Turkey Economic Monitor, May 2018 : Minding the External Gap - World Bank Group (World Bank, Washington, DC, 2018)
A strong policy response - on the back of fiscal buffers, a strong financial system, and favorable external conditions - enabled Turkey to recover from its shock of 2016, with growth accelerating to 7.4 percent in 2017. The outcome of supply constraints and demand impulse are reflected in high inflation; a large current account deficit; and currency volatility. The developments are weighing on private sector confidence despite the ongoing boost to sales, employment, and profits. Enabling an orderly adjustment is important for productivity and potential output. Turkey has been prone to large economic swings in the past. The greater the volatility in growth, the more pronounced is the negative impact on productive investment and efficiency of resource allocation. The possibility for monetary policy to respond to adverse external developments is more challenging. A combination of high inflation (due to demand pressures, exchange rate passthrough, and higher production costs) on the one hand, and rising (and positive) policy rates on the other, creates challenges for a monetary stimulus in the event of an external shock. This challenge is exacerbated by the need to cool credit expansion, which has been above its long-term trend.